2007
DOI: 10.1158/1078-0432.ccr-07-0410
|View full text |Cite
|
Sign up to set email alerts
|

An Open-Label, Two-Arm, Phase I Trial of Recombinant Human Interleukin-21 in Patients with Metastatic Melanoma

Abstract: Purpose: Human interleukin-21 (IL-21) is a pleiotropic class I cytokine that activates CD8 + T cells and natural killer cells.We report a phase 1study of recombinant human IL-21in patients with surgically incurable metastatic melanoma. The primary objective was to investigate safety and tolerability by determining dose-limiting toxicity (DLT). The secondary objectives were to identify a dose response for various biomarkers in the peripheral blood, estimate the minimum biologically effective dose, determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
130
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(144 citation statements)
references
References 30 publications
(16 reference statements)
10
130
0
1
Order By: Relevance
“…In the current study, we administered IL-21, a potent immunomodulatory cytokine, to ART-treated, (16). Last, IL-21 is currently being evaluated in several phase I and II cancer clinical trials, with limited toxicity and encouraging single-agent activity (17,(47)(48)(49). Importantly, a historic limitation of the SIV/RM model for studies of HIV residual disease, i.e., the lack of an optimized ART that fully suppresses virus replication, has been recently overcome, with a number of studies showing that the combination of tenofovir, emtricitabine, an integrase inhibitor (raltegravir or dolutegravir), and darunavir can durably suppress SIV infection of RMs to clinically relevant levels (50-53).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we administered IL-21, a potent immunomodulatory cytokine, to ART-treated, (16). Last, IL-21 is currently being evaluated in several phase I and II cancer clinical trials, with limited toxicity and encouraging single-agent activity (17,(47)(48)(49). Importantly, a historic limitation of the SIV/RM model for studies of HIV residual disease, i.e., the lack of an optimized ART that fully suppresses virus replication, has been recently overcome, with a number of studies showing that the combination of tenofovir, emtricitabine, an integrase inhibitor (raltegravir or dolutegravir), and darunavir can durably suppress SIV infection of RMs to clinically relevant levels (50-53).…”
Section: Discussionmentioning
confidence: 99%
“…An assessment of DNAM-1 ligand (CD155) and other ligand (CD70, CD80, MICA/B) status and lung metastases response to IL-2 in patients beckons. IL-21 has been examined clinically in phase I trials in patients with malignant melanoma and renal cell carcinoma and has a superior safety profile compared with IL-2 (49,50). Although IL-21 has now entered various phase II trials (5), the importance of DNAM-1 and their tumor ligands in the NK cell effector function and antitumor activity of this cytokine in humans remains unknown.…”
Section: The Journal Of Immunology 907mentioning
confidence: 99%
“…A phase I study involving IL-21 monotherapy for metastatic melanoma or renal cell carcinoma reported that monotherapy was well tolerated and exhibited anti-tumour activity in some patients (Davis et al, 2007;Thompson et al, 2008), thereby suggesting that IL-21 may have an anti-tumour effect as a monotherapy. However, this study clearly showed that IL-21 could efficiently enhance impaired ADCC activity in ESCC patients, suggesting that combination therapy of Trastuzumab or Cetuximab with IL-21 might result in the enhancement of the anti-tumour effect.…”
Section: Discussionmentioning
confidence: 99%